Magnetisation transfer, T1 and T2* relaxation in canine menisci of elderly dogs—an ex vivo study in stifle joints - Bunzendahl, Lena; Moussavi, Amir; Bleyer, Martina; Neumann, Stephan; Boretius, Susann (Frontiers in Veterinary Science, 2025)
Magnetic resonance imaging (MRI) is widely used in human medicine, offering multiple contrast mechanisms to visualise different tissue types. It is also gaining importance in veterinary medicine, including diagnosing joint disorders. The menisci of the stifle joint play a crucial role in the development of osteoarthritis (OA), and multi-parameter MRI of the menisci may aid in early OA diagnosis, potentially improving therapeutic outcomes. In a previous ex vivo study, we measured T2 relaxation times in menisci of elderly dogs with mild histological signs of degeneration but no clinical symptoms of lameness. As no significant changes in T2 relaxation times were observed in relation to histological scores, the present study extends this investigation by exploring more advanced MR parameters—including T1 relaxation time, T2* relaxation time, magnetisation transfer ratio (MTR), and magnetisation transfer saturation (MTsat)—to assess their potential for detecting early microstructural changes in the menisci. While T2* relaxation times and MTR showed no significant variation across histological scores, MTsat values increased with higher proteoglycan staining. In contrast, the apparent T1 relaxation time (T1app) was lower in menisci with elevated proteoglycan scores and increased with higher cellularity scores. The correlation between MTsat and proteoglycan content suggests that MTsat, along with T1app, could be a promising parameter for characterising the extracellular matrix. However, further research is needed to validate these findings.